English Variation Used In Reading Class At Higher Education In East Kalimantan - Febiyani; Bibit Suhatmady; Iwan Setiawan (Borneo Educational Journal (Borju), 2024)
This study aims to identify the English accents that students use in English reading class and their perceptions about English accents in Indonesia. The research employed a qualitative design to elicit more detailed answers and utilized a modified interview as a research instrument. The researcher enlisted 38 students of English Language Education from a private university in East Kalimantan as participants in this study. Four out of the 38 students were selected for interviews. The results of the research indicated that 9.5% (N=34) participants used an American accent and 10.5% (N=4) participants used a British accent when reading a text in English. The interview result showed that American English was the favored accent for reading and general perception, likely due to its popularity and perceived ease in the media. Despite these preferences, students acknowledged British English as a formal and distinguished accent. They agreed that exposure to different dialects can help in speaking, listening, and vocabulary development. Media exposure played a significant role in influencing their accents.